(untitled) (Research, Society and Development, 2022)
This article aimed to understand how municipal public schools in the city of São Luís/MA promote the inclusion of people with disabilities through their multifunctional resource rooms. The methodology used was the qualitative approach, where several documental analyzes took place, reflecting different lines of research on this topic. The research results point to a robust legislation on education at national and state level for special education, however, in the municipality in question, few points related to this discussion were found, which hypothetically suggests that the implementation of these policies in schools, too, is absent. And as propositions, pedagogical proposals were elaborated in order to contribute to the reflection of teachers and students, regarding issues related to special and inclusive education.